Identification of Yeast Species in Sompuk, a Fermented Vegetable from Vientiane Markets, Lao PDR - Yialee, Yanglao; Surawang, Suthat; Wirjantoro, Tri Indrarini (Food and Applied Bioscience Journal, 2018)
Sompuk is Lao fermented vegetable made from mustard green, white cabbage, green onion, cooked skin of cow, salt and some flavoring. In this study, 27 samples comprised of three types of Sompuk, including Sompukkard, Sompukalam and Sompukboua, were obtained from three fresh markets in Vientiane, namely Khuadin, Thongkhankham, Thatluang. All Sompuk samples were determined for the presence of yeast in the products. The results revealed that the fermented vegetable had a range of yeast from 2.26 to 4.67 log CFU/g. After purification and identification, eight species of yeast, namely Candida globosa, C. utilis, C. valida, Rhodotorula glutinis, Sporobolomyces salmonicolor, Saccharomyces cerevisiae, Schwanniomyces etchellsii and Zygosaccharomyces spp., could be recognized from the Sompuk samples. Some of these yeasts have been applied in food and beverages fermentation. However, the presence of these yeasts in Sompuk products might have a role as spoilage microorganisms.